Tropical/Subtropical Peatland Development and Global CH(4) during the Last Glaciation - Xu, Hai (Sci Rep, 2016)
Knowledge of peatland development over the tropical/subtropical zone during the last glaciation is critical for understanding the glacial global methane cycle. Here we present a well-dated ‘peat deposit-lake sediment’ alternate sequence at Tengchong, southwestern China, and discuss the peatland development and its linkage to the global glacial methane cycle. Peat layers were formed during the cold Marine Isotope Stage (MIS)-2 and -4, whereas lake sediments coincided with the relatively warm MIS-3, which is possibly related to the orbital/suborbital variations in both temperature and Asian summer monsoon intensity. The Tengchong peatland formation pattern is broadly synchronous with those over subtropical southern China and other tropical/subtropical areas, but it is clearly in contrast to those over the mid-high Northern Hemisphere. The results of this work suggest that the shifts of peatland development between the tropical/subtropical zone and mid-high Northern Hemisphere may have played important roles in the glacial/interglacial global atmospheric CH(4) cycles.